Usage of A Virtual Environment to Improve the Teaching of Fluid Mechanics - Boettcher, Konrad; Behr, Alexander (International Journal of Online and Biomedical Engineering (iJOE), 2020)
In many fields of study, physical sub-areas are treated mathematically in order to teach students the tools for optimization in their professional lives. This often means that the understanding of the physical interrelationships is left out in the cold. Practical experiments are often unsuitable for clarification, since important quantities in the mathematical formulation cannot be made visible in experiments (or only with extreme effort). Numerical calculations may show these quantities, but students cannot carry them out for themselves. For this purpose, the software Unreal engine 4 is used to create a virtual environment for fluid mechanics and compared with other methods to improve the teaching of the fundamentals of fluid mechanics. The virtual environment enables the students to influence the flow in order to experience and examine the basic physical effects. The results were used and evaluated in exercises and tutorials associated to the fluid mechanics course. Benefits for the use of virtual reality (VR) in teaching were ascertained.